PROSPECT IDENTIFICATION AT PRE-TAF CARBONATE ROCK INTERVAL IN THP AREA, ONWJ BLOCK - Hapsari, Tika
In the Northwest Java Basin, hydrocarbon exploration and production activities have been carried out, especially the reservoir intervals of the Parigi Formation, Upper Cibulakan Formation, Baturaja Formation, and Talang Akar Formation. Prospecting at new intervals continues as knowledge about this basin develops. This continued exploration activity was triggered by the discovery of new intervals containing hydrocarbons, in older stratigraphic positions that were previously considered part of the bedrock. This can be proven in one of the drilled wells, namely THP-11 which found hydrocarbons in Eocene rock called as the pre-Talang Akar Formation (pre-TAF). Therefore, this interval is interesting to study further to find other prospects in the Northwest Java Basin. In this research, the data used in this research are 3D seismic data with an area of 278341.87 Acre, wireline log data on wells THP-1, THP-11, THP-18, THP-21, and PJM-1, core rock data on wells THP-1 and PJM-1, and biostratigraphic data on THP-1 well. The stages of the research carried out to determine the distribution of prospects in carbonate rocks at pre-TAF intervals in the research area are, Seismic facies analysis which is integrated with the creation of depth structure maps is used to identify prospects for carbonate rocks. Petrophysical analysis to determine the properties of carbonate rocks as reservoirs, namely, shale volume volume and porosity. Based on the results of seismic mapping and interpretation of its character, the distribution of pre-TAF carbonate rocks is segmented by a north-south structure pattern formed after the Eocene. There are 12 prospects that can be mapped at the interval of pre-TAF carbonate rock in the form of Carbonate build-up which can be categorized into 2 types of deposition, namely platform margin and pinnacle reef on the slope. Based on the results of petrophysical analysis, the porosity value of carbonate rocks ranges from 2% - 9% which is dominated by secondary porosity of the vgular type and possibly also the natural fracture type.